Student personality development in the process of teaching physics (Pedagogy of Higher and Secondary Education, 2012)
Holodenko O. M. Student personality development in the process of teaching physics.The article deals with ways to enhance students cognitive activities in physics classes, revealed the benefits of design technology in the development of individual pupils.
Keywords: cognitive interest; project method; activation of cognitive activity; the surface tension